Tubuh Perempuan dan Artificial Intelligence - Dian Ursula Yenifer Sarah (Jurnal Pendidikan Kristen dan Ilmu Teologi Marturia, 2023)
Abstract Nowadays, the flow of information and developments in the world of science is both an opportunity and a challenge that all elements continue to face. The world of theology is no exception, especially when facing various latest discoveries in the scientific world, for example, a technology called Artificial Intelligence or artificial intelligence. Departing from this, this paper aims to analyze the position of humans in terms of women's bodies in the midst of the presence of sexual robots. This paper uses a qualitative methodology with literature studies. The data will be obtained from various sources of scientific literature, documents, news, or written information that has a connection. The author will conduct an analysis with a feminist perspective on the presence of sexual robots that resemble women as a result of Artificial Intelligence. From the results of the writing, it was found that by embedding Artificial Intelligence into sexual robots, the warm and intimate relationship between men and women seems to have faded. Abstrak Sekarang ini arus informasi dan perkembangan dalam dunia sains menjadi peluang sekaligus tantangan yang terus dihadapi oleh semua elemen manusia. Tidak terkecuali dunia teologi, khususnya ketika menghadapi berbagai penemuan terbaru dalam dunia saintek misalnya teknologi yang bernama Artificial Intellegence atau kecerdasan buatan. Berangkat dari hal tersebut maka tulisan ini hendak bertujuan untuk menganalisis posisi manusia dalam hal tubuh perempuan di tengah kehadiran robot seksual. Penulisan ini menggunakan metodologi kualitatif dengan studi kepustakaan. Adapun data akan diperoleh dari berbagai sumber literatur ilmiah, dokumen, berita atau informasi tertulis yang memiliki keterkaitan. Penulis akan melakukan analisis dengan perspektif feminis terhadap kehadiran robot seksual yang menyerupai perempuan sebagai hasil dari Artificial Intellegence. Dari hasil penelitian ditemukan bahwa dengan menyematkan Artificial Intellegence ke dalam robot seksual maka relasi hangat dan intim antara laki-laki dan perempuan seakan menjadi pudar.